2016
DOI: 10.1017/s0021932016000237
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Intestinal Schistosomiasis Among Fisherfolk Living Along the River Nile in North-Western Uganda: A Biosocial Investigation

Abstract: SummaryMass drug administration has been less successful as a technique for controlling intestinal schistosomiasis (S. mansoni) than anticipated. In Uganda, the mass distribution of praziquantel has been provided to populations at risk of infection since the early 2000s, but prevalence mostly remains high. This is the case, for example, at locations in north-western and south-eastern Uganda. However, there is a remarkable exception. Among Madi fishing populations and their immediate neighbours, living close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…The adherence rate to the drug treatment in this research was satisfactory, above the rate advised by the (80%) Ministry of Health even having initially aversion to the use of the Praziquantel drug due to its side effects (headache, vomiting, diarrhea, fever, muscular and articular pain, among others), condition also reported in fishermen population resident in endemic areas for the schistosomiasis in the African continent. 49 The reluctance to the use of Praziquantel may be related to the sharing, in the community under study in Alagoas, of the sensations and experiences lived by individuals who adhered and were in drug treatment, provoking in those who did not adhere to the chemotherapy a ripple effect of fear to the anti-parasite drug.…”
Section: Discussionmentioning
confidence: 99%
“…The adherence rate to the drug treatment in this research was satisfactory, above the rate advised by the (80%) Ministry of Health even having initially aversion to the use of the Praziquantel drug due to its side effects (headache, vomiting, diarrhea, fever, muscular and articular pain, among others), condition also reported in fishermen population resident in endemic areas for the schistosomiasis in the African continent. 49 The reluctance to the use of Praziquantel may be related to the sharing, in the community under study in Alagoas, of the sensations and experiences lived by individuals who adhered and were in drug treatment, provoking in those who did not adhere to the chemotherapy a ripple effect of fear to the anti-parasite drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 2013, one of our research team documented the prevalence of S. mansoni among these fishing families, and found it to be below 4%. The prevalence of soil-transmitted helminths was also low -ranging from 0% at the majority of sites to 11% at the worst affected location (Pearson, 2016). Thus, despite the variable coverage levels in schools and in the general population, the prevalence of infection with intestinal helminths is at a lower level than might be expected.…”
Section: Mass Drug Administration In East African Schools S135mentioning
confidence: 82%
“…In other words, deworming alone was largely ineffective. Since 2005, research undertaken by the authors and their students has found comparable problems in other parts of East Africa (Aldis, 2008;Wingate-Saul & Shira, 2008;Parker et al, 2008Parker et al, , 2012Parker & Allen, 2011, 2013aOzunga, 2014;Pearson, 2016;Hastings, 2016). Field sites were located in north-western Uganda (Nebbi, Buliisa, Adjumani and Moyo Districts), south-eastern Uganda (Busia District -just across the border from where Miguel and Kremer studied deworming in Kenya), Tanzania's Ukerewe Island in Lake Victoria, Tanga Region in northern coastal Tanzania, and Morogoro Region, which lies to the west of Dar es Salaam (see Fig.…”
Section: Doing Deworming In East Africamentioning
confidence: 90%
“…The broader study included an epidemiological-parasitology survey conducted in collaboration with the District Vector Control Division of the Ministry of Health. This was of adults at twelve fish landing sites, one from each sub-county along the river and one island, investigating another neglected disease, schistosomiasis, (documented elsewhere [ 26 ]).This article presents findings that emerged from the ethnographic fieldwork related to Buruli ulcer, as documented in ethnographic fieldnotes, interviews and discussions.…”
Section: Methodsmentioning
confidence: 99%